Gastrointestinal helminths of two populations of wild pigeons (Columba livia) in Brazil - Vaz, Frederico Fontanelli; Silva, Lidiane Aparecida Firmino Da; Ferreira, Vivian Lindmayer; Silva, Reinaldo José Da; Raso, Tânia Freitas (Colégio Brasileiro de Parasitologia Veterinária, 2017)
Abstract The present study analyzed gastrointestinal helminth communities in 265 wild pigeons (Columba livia) living in the municipalities of São Paulo and Tatuí, state of São Paulo, Brazil, over a one-year period. The birds were caught next to grain storage warehouses and were necropsied. A total of 790 parasites comprising one nematode species and one cestode genus were recovered from 110 pigeons, thus yielding an overall prevalence of 41.5%, mean intensity of infection of 7.2 ± 1.6 (range 1-144) and discrepancy index of 0.855. Only 15 pigeons (5.7%) presented mixed infection. The helminths isolated from the birds were Ascaridia columbae (Ascaridiidae) and Raillietina sp. (Davaineidae). The birds’ weights differed according to sex but this did not influence the intensity of infection. The overall prevalence and intensity of infection did not differ between the sexes, but the prevalence was higher among the birds from Tatuí (47.8%). The gastrointestinal helminth community of C. livia was characterized in the two areas studied and parasite homogeneity was observed over the 12 months analyzed at both locations. These results make contributions to the current literature on health aspects of wild C. livia populations.

Resumo O presente estudo analisou comunidades gastrointestinais de helmintos em 265 indivíduos de Columba livia de vida livre nos municípios de São Paulo e Tatuí, estado de São Paulo, Brasil, durante um ano. As aves foram capturadas em áreas de armazenamento de grãos e sementes e necropsiadas. Um total de 790 parasitos representando uma espécie de nematódeo e um gênero de cestoide foram recuperados de 110 pombos com uma prevalência geral de 41,5%, intensidade média de infecção de 7,2 ± 1,6 (amplitude 1-144) e índice de discrepância de 0,855. Somente 15 (5,7%) pombos tiveram uma infecção mista. Os helmintos isolados das aves foram Ascaridia columbae (Ascaridiidae) e Raillietina sp. (Davaineidae). O peso das aves foi diferente entre os sexos, mas não influenciou a intensidade de infecção. A prevalência geral e a intensidade de infecção não foram diferentes entre sexo, mas a prevalência foi maior nas aves de Tatuí (47,8%). A comunidade gastrointestinal de helmintos de C. livia foi caracterizada nas duas áreas estudadas e uma homogeneidade de parasitos foi observada nos 12 meses analisados, em ambas localidades. Os resultados contribuem para a literatura atual sobre aspectos sanitários de populações de C. livia em vida livre.
Helmintos gastrointestinais de duas populações de pombos de vida livre (Columba livia) no Brasil
Keywords: Columbiformes; helminthology; nematodes; cestodes; Ascaridia; Raillietina; Columbiformes; helmintologia; nematódeos; cestódeos; Ascaridia; Raillietina